Diagnósticos de enfermería en pacientes atendidos en trauma shock de un hospital publico: factores asociados - Valles Flores, Mercedes Natividad (2024)
This study will use the quantitative, observational, prospective, cross-sectional descriptive and correlational method; with the objective of determining the factors associated with nursing diagnoses in patients attended in trauma shock of a public hospital. The population will consist of all patients admitted to the trauma shock unit of the emergency department of the Regional Hospital of Loreto. As techniques, the patient's clinical history will be reviewed and the patient and/or family member will be investigated. The data collection instruments will be a questionnaire where the sociodemographic and clinical variables will be put, for nursing diagnoses will use the checklist according to Nanda 2021-2023 that will be developed by the researcher and advisor, for its validity 5 specialist nurses will be selected to perform the expert judgment, as reliability, the equivalence test will be.